2015
DOI: 10.1007/s11743-015-1752-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Properties of Novel Cationic Gemini Surfactants with Rigid Amido Spacer Groups

Abstract: A series of novel cationic gemini surfactants with rigid amido groups inserted as the spacers, named C12‐PPDA‐C12, C14‐PPDA‐C14 and C16‐PPDA‐C16, were synthesized by a two‐step reaction with dimethyl terephthalate, N,N‐dimethyl propylene diamine and alkyl bromide as raw materials. The chemical structures of the prepared compounds were confirmed by IR, 1H and 13C NMR and element analysis. Surface activity properties of the synthesized compounds were investigated by surface tension, electrical conductivity and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
(63 reference statements)
2
9
0
Order By: Relevance
“…However, the emulsification power presents a slight change when the concentrations rise to 5.0 g L −1 , where the order is CTASE<CTASU<CTAA<CTAG<CTAO<CTAM. The result is in good agreement with the reported general tendency that the surfactant solution concentration can directly exert a different influence on the emulsification power (Xu et al, ). Seen from Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, the emulsification power presents a slight change when the concentrations rise to 5.0 g L −1 , where the order is CTASE<CTASU<CTAA<CTAG<CTAO<CTAM. The result is in good agreement with the reported general tendency that the surfactant solution concentration can directly exert a different influence on the emulsification power (Xu et al, ). Seen from Fig.…”
Section: Resultssupporting
confidence: 92%
“…This means that the synthesized 3C n taDA have weak emulsifying power, and that they cannot be used as emulsifiers. This result is in accordance with those of other oligomeric surfactants (Hu et al, 2016;Tai et al, 2012;Xu et al, 2015).…”
Section: Emulsion Stabilitysupporting
confidence: 92%
“…This value is less than that of A min of sodium laurate (0.69 nm 2 ), and this means that the 3C 12 taDA molecules arrange more tightly in the interfacial film, and that the mechanical strength of formed interfacial film is higher. The long alkyl chains of the surfactant molecules have a strong hydrophobic effect and enhance the ability to damage the structure of the water phase (Xu et al, ). The strong interaction between long alkyl chains can increase the viscoelasticity of the interfacial film, hence, improve the mechanical strength of the film (Mohd et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Gemini surfactants with the double bond in the trans ‐configuration showed better surface properties than the cis ‐isomers. Liu et al () and Xu et al () reported on the preparation, characterization, and properties of cationic Gemini surfactants with rigid spacer groups. The Gemini surfactants show enhanced surface activity and emulsification properties.…”
Section: Conflict Of Interestmentioning
confidence: 99%